2021
DOI: 10.1167/iovs.62.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Observation of Border Tissue Configuration During Axial Elongation in Childhood

Abstract: Purpose To investigate the change of border tissue configuration during axial elongation in childhood. Methods Fifty-four subjects (108 eyes; age range, 29.3–132.5 months) who had undergone a series of swept-source optical coherence tomography scans at intervals of 6 months or longer were classified into stable axial length (AXL) eyes ( n = 55; AXL change of ≤0.36 mm) and elongating AXL eyes ( n = 53; AXL change of >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…This report is the first to longitudinally study ONH neural canal remodeling in a young adult through the progression of early refractive myopia. While its findings are compatible with previous cross-sectional 3 , 4 and longitudinal 5 , 6 studies in highly myopic eyes, it differs from those studies in that the neural canal remodeling occurs in both eyes of a young adult subject that is experiencing the earliest changes of myopia.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This report is the first to longitudinally study ONH neural canal remodeling in a young adult through the progression of early refractive myopia. While its findings are compatible with previous cross-sectional 3 , 4 and longitudinal 5 , 6 studies in highly myopic eyes, it differs from those studies in that the neural canal remodeling occurs in both eyes of a young adult subject that is experiencing the earliest changes of myopia.…”
Section: Discussionsupporting
confidence: 83%
“…The development of optic coherence tomography (OCT) has allowed a better understanding of the prelaminar ONH neural canal tissues, which extend from BMO through the choroidal border tissues of Elschnig, the anterior scleral canal opening (ASCO) and the deeper scleral flange. 1 , 2 While cross-sectional 3 , 4 and longitudinal 5 , 6 studies have detected temporal displacement and enlargement of BMO relative to ASCO in high myopia, the longitudinal studies to date have concentrated on childhood myopia in highly myopic eyes. This report is the first longitudinal OCT study of ONH neural canal remodeling in young adult eyes through the progression of early refractive myopia.…”
Section: Introductionmentioning
confidence: 99%
“…Another study 8 from the same group demonstrated that during axial elongation, the temporal border tissue length stretches to the nasal side while its angle changes from internally oblique to externally oblique. Kim et al 6 previously discovered that with elongation of axial-length, nasal MRW increases, which suggests that nasal peripapillary tissue elevation occurs with progression of myopia. Our findings can supplement results from previous studies on myopic ONH change, especially with regard to three-dimensional change of LC curvature.…”
Section: Discussionmentioning
confidence: 98%
“… 3 5 Currently, myopic optic nerve head (ONH) features are being further studied by optical coherence tomography (OCT). Kim et al 6 demonstrated that as axial elongation procedes, the temporal border tissue changes to externally oblique, the Bruch’s membrane opening (BMO) enlarges, and the nasal minimum rim width (MRW) elevates.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies considered Bruch's membrane (BM) as the biomechanically supporting structure and the primary driver elongating the globe (Jonas et al 2017;Wu et al 2019;Jonas et al 2020), whereas there is little information on morphological characteristics of the optic nerve head, especially on ultra-structural changes related to BM in highly myopic eyes of young adults during myopia progression. Previous two prospective cohort studies conducted in Korea demonstrated that temporal border tissue configuration changed during axial elongation in childhood (Kim et al 2018;Kim et al 2021). However, the impact of border tissue (BT) configuration characteristics on choroidal thickness (ChT) remains unclear.…”
Section: Introductionmentioning
confidence: 99%